2018
DOI: 10.1029/2018ja026014
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐6‐Day Wave Effects on the Equatorial Ionization Anomaly Over a Solar Cycle

Abstract: The quasi-6-day wave (Q6DW) has recently been recognized as an important source of ionospheric variability. This study shows how the response of the equatorial ionosphere to the Q6DW changes over a solar cycle. Global maps of total electron content (TEC) from Global Positioning System data are used to quantify Q6DW effects on the equatorial ionization anomaly during 2004-2017. The results are compared with the Q6DW amplitude in the lower thermosphere as derived from the geopotential height measurements by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 42 publications
6
52
1
Order By: Relevance
“…Such enhanced wave activity is not present in the eastward propagating ZW1 component (Figure b) or other components with higher ZWs (not shown here). Although studies have found that the amplitude of the Q6DW in the middle atmosphere is greatest during equinoctial months (Forbes & Zhang, ; Qin et al, ; Yamazaki, ), the wave enhancement in September 2019 was exceptional, with the maximum amplitude larger than 0.4 km in the lower thermosphere, which is much larger than the climatological amplitude (0.15 km) or amplitudes recorded during other individual years during 2004–2018 (Figure d). Thus, the large‐amplitude Q6DW observed in September 2019 cannot be explained merely as a seasonal effect.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Such enhanced wave activity is not present in the eastward propagating ZW1 component (Figure b) or other components with higher ZWs (not shown here). Although studies have found that the amplitude of the Q6DW in the middle atmosphere is greatest during equinoctial months (Forbes & Zhang, ; Qin et al, ; Yamazaki, ), the wave enhancement in September 2019 was exceptional, with the maximum amplitude larger than 0.4 km in the lower thermosphere, which is much larger than the climatological amplitude (0.15 km) or amplitudes recorded during other individual years during 2004–2018 (Figure d). Thus, the large‐amplitude Q6DW observed in September 2019 cannot be explained merely as a seasonal effect.…”
Section: Resultssupporting
confidence: 90%
“…In this way, the Q6DW can affect the F region plasma density, as first revealed in the 1990s by ionosonde measurements (e.g., Apostolov et al, ; Altadill & Laštovička, ; Laštovička, ). More recent studies based on global TEC maps have established that the Q6DW effect on the plasma density is largest in the afternoon local time sector near the equatorial ionization anomaly crests ( ±20° magnetic latitudes) (Gu et al, , ; Qin et al, ; Yamazaki, ).…”
Section: Resultsmentioning
confidence: 98%
“…The relative amplitude is used to eliminate the influences of seasonal (Figure 1d) and diurnal (Figure 1e) variations of background ionosphere. Relative amplitude is more intimately related to the Q6DW amplitude in the neutral atmosphere (Gu et al, 2018; Yamazaki, 2018), while the absolute amplitude is influenced more by the ambient ionosphere. The strongest ionospheric Q6DO in the relative amplitude accounts for ~17% of the background TEC at 12 LT.…”
Section: New Characteristics Of Ionospheric Responses To the Q6dwmentioning
confidence: 99%
“…The Q6DW has recently received elevated attention in the literature due to its demonstrated effectiveness in driving F‐region ionospheric variability (Gan et al, , ; Gu et al, ; Gu, Liu, et al, ; Gu, Ruan, et al, ; Qin et al, ; Yamazaki, ). Changes in F‐region electron densities at Q6DW periods result from transport by ExB drifts, where the electric field E is generated in the ionospheric E‐region through dynamo action of Q6DW winds and possibly Q6DW modulation of tides and/or gravity waves (e.g., Forbes, ; Meyer, ).…”
Section: Introductionmentioning
confidence: 99%